ПСИХОЛОГИЧЕСКИЕ УСЛОВИЯ УСПЕШНОСТИ ОБУЧЕНИЯ ВЗРОСЛЫХ ИНОСТРАННОМУ ЯЗЫКУ С УЧЕТОМ КОГНИТИВНЫХ СТИЛЕЙ - Силенко, Е.А.; Смаглий, Т.И. (My University, 2019)
Аннотация В статье представлен отрывок из исследования психологических условий успешности обучения взрослых иностранному языку с учетом их когнитивных стилей. Авторы дают пояснение понятийно-категориальному аппарату проблемы для полного рассмотрения сути вопроса, а также описывают возможные психологические условия, которые могут способст- вовать успешности обучения взрослых при изучении иностранного языка, основываясь на их когнитивных стилях. Abstract The article presents an excerpt from research of the psychological conditions for the succes- sfulness of adult foreign language learning, according to cognitive styles. The authors explain the conceptual for categorical apparatus of the problem for a full consideration of the essence of the issue, and also describe the possible psychological conditions that can contribute to the success- sfulness of adult learning in foreign language, based on their cognitive styles.
Psychological conditions for the successfulness of adult foreign language learning, according to cognitive styles
Keywords: когнитивный стиль; успешность обучения; иностранный язык; обучение взрослых; cognitive style; successfulness of learning; foreign language; adults learning